More answers

m = -4

Q: What is the answer to m plus 1 equals -3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

m = 31m + 9 = 1(3) + 9 = 3 + 9 = 12

m= -3

Given m equals 3 and n equals 1 then m3n3 equals?m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]

m = n/(n-1)

m= -77/5

Related questions

4!

m = 1

m = 31m + 9 = 1(3) + 9 = 3 + 9 = 12

m= -3

Given m equals 3 and n equals 1 then m3n3 equals?m3n3 = m*3*n*3 = 3*3*1*3 = [ 27 ]

m = n/(n-1)

m= -77/5

m = 3

5/8 plus m = 1 easy4/4=167/67=18/8=1m=3/8

commutative property of addition

40

If: 9m+2m = 33 Then: m = 3